2011
DOI: 10.1007/s10802-011-9528-0
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Children’s ADHD Symptoms and Parenting Stress: A Multiple Mediation Model of Self-Regulation

Abstract: The goal of the current study was to determine the extent to which the perceived self-regulation deficits across behavioral, cognitive, and emotional domains seen in children with ADHD explain the association between the severity of ADHD symptoms and parenting stress. Participants for this study included 80 children (mean age = 10 years, 9 months) with a DSM-IV diagnosis of ADHD confirmed by a comprehensive clinical diagnostic assessment. Parents reported their own stress levels as well as the severity of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 83 publications
(100 reference statements)
7
62
0
7
Order By: Relevance
“…For example, when ODD/CD symptoms were included in statistical models, other childhood clinical symptoms, such as attention-deficit/hyperactivity disorder were found to be unrelated to parenting [9,10]. Moreover, Podolski and Nigg [10] examined children ages 7 to 12 years and noted differences between mothers and fathers in relation to parenting-related stress.…”
Section: Childhood Callous-unemotional Traits Moderate the Relation Bmentioning
confidence: 99%
“…For example, when ODD/CD symptoms were included in statistical models, other childhood clinical symptoms, such as attention-deficit/hyperactivity disorder were found to be unrelated to parenting [9,10]. Moreover, Podolski and Nigg [10] examined children ages 7 to 12 years and noted differences between mothers and fathers in relation to parenting-related stress.…”
Section: Childhood Callous-unemotional Traits Moderate the Relation Bmentioning
confidence: 99%
“…Research has demonstrated that parenting a child with ADHD is more stressful, than parenting one without ADHD (Anastopoulos, Sommer, & Schatz, 2009;Graziano, McNamara, Geffken, & Reid, 2011;Johnson & Reader, 2002;Podolski & Nigg, 2001). A recent study noted that parents of children with ADHD reported higher stress levels than those with other chronic medical conditions, such as HIV-infection and asthma, suggesting that the parenting demands among this population are severe (Gupta, 2007).…”
Section: Parenting Behaviorsmentioning
confidence: 99%
“…Si bien se han desarrollado diversos estudios de investigación tendientes a indagar el estrés parental y los estilos educativos parentales (Pimentel, Vieira-Santos, Santos y Vale, 2011;Graziano, McNamara, Geffken y Reid, 2011;Tan, Camras, Deng, Zhang y Lu, 2012;Park y Walton-Moss, 2012), las relaciones existentes entre el estilo parental y las estrategias de afrontamiento han sido escasamente estudiadas, ya que en su mayoría se han centrado en las estrategias de afrontamiento de los niños (Richaud, 2005).…”
Section: Introductionunclassified